FluConvert and IniFlu: a suite of integrated software to identify novel signatures of emerging influenza viruses with increasing risk - Chin-Rur Yang; Chwan-Chuen King; Li-Yu Daisy Liu; Chia-Chi Ku (BMC Bioinformatics, 2020)
Abstract Background The pandemic threat of influenza has attracted great attention worldwide. To assist public health decision-makers, new suites of tools are needed to rapidly process and combine viral information retrieved from public-domain databases for a better risk assessment. Results Using our recently developed FluConvert and IniFlu software, we automatically processed and rearranged sequence data by standard viral nomenclature, determined the group-related consensus sequences, and identified group-specific polygenic signatures. The software possesses powerful ability to integrate viral, clinical, and epidemiological data. We demonstrated that both multiple basic amino acids at the cleavage site of the HA gene and also at least 11 more evidence-based viral amino acid substitutions present in global highly pathogenic avian influenza H5N2 viruses during the years 2009–2016 that are associated with viral virulence and human infection. Conclusions FluConvert and IniFlu are useful to monitor and assess all subtypes of influenza viruses with pandemic potential. These programs are implemented through command-line and user-friendly graphical interfaces, and identify molecular signatures with virological, epidemiological and clinical significance. FluConvert and IniFlu are available at https://apps.flutures.com or https://github.com/chinrur/FluConvert_IniFlu